2016
DOI: 10.1177/0284185116658322
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound (CEUS) in assessing early response among patients with invasive breast cancer undergoing neoadjuvant chemotherapy

Abstract: Background One of the big challenges in onco-radiology is to find a reliable imaging method that may predict early response during the first cycles of any neoadjuvant chemotherapy. Purpose To evaluate the use of real-time harmonic contrast-enhanced ultrasound (CEUS) in predicting early response in breast cancer tumors under neoadjuvant chemotherapy (NAC) treatment. Material and Methods Nineteen consecutive patients with invasive breast cancer were evaluated with a bolus dose of 2.4 mL contrast agent using CEUS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 20 publications
(24 reference statements)
3
26
0
Order By: Relevance
“…The ability of CEUS to predict a pathological complete response in patients with breast cancer who have received NAC has been reported previously [20][21][22][23][24][25]. In a study of 63 patients, Amioka et al [20] reported that both the peak intensity and the ascending slope were significantly lower in those who achieved a pathological complete response than in those who did not.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The ability of CEUS to predict a pathological complete response in patients with breast cancer who have received NAC has been reported previously [20][21][22][23][24][25]. In a study of 63 patients, Amioka et al [20] reported that both the peak intensity and the ascending slope were significantly lower in those who achieved a pathological complete response than in those who did not.…”
Section: Discussionmentioning
confidence: 68%
“…b After the first cycle of NAC, the wash-out rate on ROI 1/4 was 53 au and the AUC was 0.81 (p = 0.001) with a cut-off value of 29.58. tumor contour. In another study that included 19 patients, Saracco et al [23] concluded that the TTP was significantly longer in responders after two cycles on the whole tumor ROI at week 5 than at the baseline scan when compared with non-responders. However, unlike the previous data, the data obtained before and after the first NAC cycle in our study had no significant ability to predict the tumor response to NAC by peak enhancement or TTP for any of the six ROIs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, in human renal carcinomas, TTP was shorter compared to normal kidneys and malignant breast cancer was differentiated from benign lesions by a significantly reduced TTP . Saracco et al recently showed that TTP can indicate responsiveness to neoadjuvant chemotherapy in invasive breast cancer. The diagnostic value of TTP for objective, quantitative diagnosis and monitoring in canine ocular and orbital neoplasias deserves further study.…”
Section: Discussionmentioning
confidence: 99%
“…These changes may occur earlier than a reduction in tumor size. Nonetheless, previous reports have not fully evaluated the reproducibility of CEUS [17,20,21,23,25] and debate persists regarding the most appropriate region of interest (ROI) for quantitative analysis of the time-intensity curve (TIC) [9,21,24].…”
Section: Introductionmentioning
confidence: 99%